On the biology of blackbellied angler, Lophius budegassa Spinola, 1807, in the north-western Mediterranean - MASSARO, ANDREA; MUSUMECI, CLAUDIA; De CARLO, FRANCECO; LIGAS, ALESSANDRO; RUSSO, LOREDANA; CARBONARA, PIERLUIGI; PRETTI, CARLO; SARTOR, PAOLO (Mediterranean Marine Science, 2024)
In the Mediterranean Sea, the blackbellied angler, Lophius budegassa Spinola, 1807, represents a relevant fraction of the commercial by-catch of bottom trawling and small-scale fisheries that use passive gears (e.g., set nets, bottom longlines, etc.). Despite its importance, there are no comprehensive studies on the population dynamics of this species, and there is still scarce and scattered knowledge of its biology and ecology. Biomass, morphometric, and biological data of the blackbellied angler were collected from 1994 to 2021 by means of the Mediterranean International Bottom Trawl Survey (MEDITS) programme in the Ligurian and northern Tyrrhenian Seas, and in the EU Data Collection Framework during the period of 2006-2021. Furthermore, ageing was performed on specimens collected from 2013 to 2021 during the MEDITS programme. There were high values for the density indices and the spatial distribution of biomass in the central sector of the investigated area (the Tuscan Archipelago), mostly on the continental shelf. The length-weight relationship showed negative allometric growth when considering the sexes together, and no difference between the sexes. The size at first maturity (L50) was estimated at 39.4 cm total length (TL) in females and at 29.2 cm TL in males. The obtained Von Bertalanffy growth parameters were: in females, L∞ = 74.50 cm, k = 0.10 years-1, and t0 = -0.40 years; in males, L∞ = 61.30 cm, k = 0.14 years-1, and t0 = -0.38 years. There were differences in growth between males and females for L∞ (χ2 = 10.04; p < 0.05) and k (χ2 = 6.12; p < 0.05).